Guia de árvores da arborização pública de Campina do Monte Alegre-SP - Rigoli, Vitor Sergio Lourenço (Universidade Federal de São Carlos, 2024)
Due to the intense process of urbanization and the loss of native vegetation, the presence of trees in urban centers provides numerous benefits to the lives of the population, leading to improvements in physical and social well-being, and regulating microclimatic conditions. Furthermore, they create an opportunity for survival of fauna, providing shelter and food, contributing to the maintenance of animal and plant biodiversity. However, the lack of adequate management can cause several social, economic and ecological problems. The city of Campina do Monte Alegre is located in a transitional region between the Cerrado and the Atlantic Forest domains. The municipality presents a landscape of increasing urbanization, and large areas dedicated to agriculture and forestry. Thus, the present work consisted of preparing a didactic guide, through a survey of the city's public urban afforestation. In this way, individuals present in public areas of the city, such as sidewalks, squares and parks, were considered. In total, 35 species were identified, 17 of which were considered exotic and 18 were native to Brazil. Therefore, the present afforestation does not represent well the natural domains of the region, as mostly of the cultivated species do not belong to the local flora. Furthermore, 11 species belong to the Fabaceae family, representing around 31% of the total, which exceeds the recommended percentage for the same group. Furthermore, species were observed that had the potential to damage public infrastructure and cause environmental imbalance, that is, they are not suitable for afforestation. Finally, greater participation and planning responsibility of public authorities, instruction to residents and prioritization of planting native species are suggested.
Guide to the trees of public afforestation in Campina do Monte Alegre-SP
Keywords: Microclimáticas; Biodiversidade; Urbanização; Cerrado; Mata Atlântica; Arborização urbana; Fabaceae; Espécies nativas; Desequilíbrio ambiental; Microclimatic; Biodiversity; Cerrado; Atlantic forest; Urban afforestation; Native species; Environmental imbalance; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL